MAIN BARRIERS AND POSSIBLE ENABLERS OF GOOGLE APPS FOR EDUCATION ADOPTION AMONG UNIVERSITY STAFF MEMBERS (Nigerian Journal of Technology, 2018)
Understanding users’ acceptance is a key factor for the development and success of Educational Technologies (ETs), as access to these technologies alone does not guarantee use, nor does it determine the benefit for the intended user. This study aimed to investigate the issue with acceptance and use of Google Apps for Education (GAFE) and examine factors that influence and predict acceptance and use among University of Benin Staff Members. A sample of 200 University staff members took part in the research. The structural equation modeling (SEM) technique was employed to describe the adoption process. The result revealed that GAFE facilitating condition was the most important construct, followed by performance expectancy in explicating the causal process in the model to assess the acceptance and use of Google Apps for Education. http://dx.doi.org/10.4314/njt.v37i2.18